CURRENT USE OF NANOPARTICLES IN ENDODONTICS: A SYTEMATIC REVIEW - Andreea Marica; Lucian Sipos; Raluca Iurcov; Teodora Stefanescu; Gabriela Ciavoi; Alexandra-Ioana Lucan; Florina Miere (Groza) (Romanian Journal of Oral Rehabilitation, 2022)
Nowadays, technology evolves very fast and we are witnesses of major changes in dentistry. Nanotechnology improved many fields of dentistry, including endodontics.